Review of guidelines and recommendations from 17 countries highlights the challenges that clinicians face caring for neonates born to mothers with COVID‐19. (20th August 2020) - Yeo, Kee Thai; Oei, Ju Lee; De Luca, Daniele; Schmölzer, Georg M.; Guaran, Robert; Palasanthiran, Pamela; Kumar, Kishore; Buonocore, Giuseppe; Cheong, Jeanie; Owen, Louise S.; Kusuda, Satoshi; James, Jennifer; et al.
Abstract: Aim: This review examined how applicable national and regional clinical practice guidelines and recommendations for managing neonates born to mothers with COVID‐19 mothers were to the evolving pandemic. Methods: A systematic search and review identified 20 guidelines and recommendations that had been published by May 25, 2020. We analysed documents from 17 countries: Australia, Brazil, Canada, China, France, India, Italy, Japan, Saudi Arabia, Singapore, South Africa, South Korea, Spain, Sweden, Switzerland, the UK and the United States. Results: The documents were based on expert consensus with limited evidence and were of variable, low methodological rigour. Most did not provide recommendations for delivery methods or managing symptomatic infants. None provided recommendations for post‐discharge assimilation of potentially infected infants into the community. The majority encouraged keeping mothers and infants together, subject to infection control measures, but one‐third recommended separation. Although breastfeeding or using breastmilk was widely encouraged, two countries specifically prohibited this. Conclusion: The guidelines and recommendations for managing infants affected by COVID‐19 were of low, variable quality and may be unsustainable. It is important that transmission risks are not increased when new information is incorporated into clinical recommendations. Practice guidelines should emphasise the extent of uncertainty and clearly define gaps in the evidence.